2005
DOI: 10.1111/j.1526-4637.2005.05036.x
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Pain in Three Chronic Pain Samples: Comparing Caucasians and African Americans

Abstract: Alexithymia is more correlated with pain severity among African Americans with chronic pain disorders than among Caucasians, potentially contributing to the higher pain reports among African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 75 publications
(77 reference statements)
6
32
0
7
Order By: Relevance
“…25 Cronbach's alpha for the TAS-EOT subscale was low (0.48) across all ethnicities in San Francisco public transit workers 25 . A low reliability for this subscale was found in other studies as well [41][42][43][44] . Alexithymia as measured by the TAS-20 is generally seen as a relatively stable trait supported by test-retest reliability of 0.74 (p < 0.001) 41 , however modifiable by psychotherapy enhanced by mindbody techniques 45 or body-oriented psychotherapy 46 .…”
Section: Measurement Of Alexithymiamentioning
confidence: 83%
“…25 Cronbach's alpha for the TAS-EOT subscale was low (0.48) across all ethnicities in San Francisco public transit workers 25 . A low reliability for this subscale was found in other studies as well [41][42][43][44] . Alexithymia as measured by the TAS-20 is generally seen as a relatively stable trait supported by test-retest reliability of 0.74 (p < 0.001) 41 , however modifiable by psychotherapy enhanced by mindbody techniques 45 or body-oriented psychotherapy 46 .…”
Section: Measurement Of Alexithymiamentioning
confidence: 83%
“…Some health professionals believe that these patients deliberately exaggerate pain (personal comments). However, severe pain could also be attributed to learned factors [6,26,36], to work load [19], emotional distress [2,12,21,22] or doctor-patient interactions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the construct of alexithymia reflecting deficits in cognitive processing and the regulation of emotions, alexithymia may play some role in pain perception. A high prevalence of alexithymia has been observed in patients with chronic pain (9), including those with RA (14,15). Numerous observational and some experimental studies revealed positive associations between alexithymia and pain intensity and sensitivity (16).…”
Section: Introductionmentioning
confidence: 99%